Sistem Informasi Manajemen Layanan Rumah Jahit Berbasis Web Menggunakan Model Waterfall dan Framework Laravel - Visa Yama; Hanriyawan Adnan Mooduto; Humaira (JITSI : Jurnal Ilmiah Teknologi Sistem Informasi, 2026)
The rapid growth of small and medium enterprises (SMEs) in the fashion and tailoring industry demands high operational efficiency to maintain customer satisfaction. One Tailor, a boutique tailoring service in Bukittinggi, conventionally managed its daily operations using manual paper-based logs. This approach created significant vulnerabilities, including data loss risks, tedious customer body measurement retrieval (taking 5–10 minutes per record), financial accounting discrepancies, and delayed garment completions due to disorganized production scheduling. This study aims to design and implement a web-based management information system specifically tailored to resolve these operational bottlenecks. Adopting the software development life cycle (SDLC) Waterfall model, the system was developed using PHP with the Laravel 10.x framework and MySQL as the relational database management system. Security measures such as Bcrypt hashing, Cross-Site Request Forgery (CSRF) protection, and role-based middleware were incorporated to protect customer confidentiality. The developed system features digital body measurement archiving, an automated notification scheduler for production deadlines, integrated financial auditing modules, and automated readiness alerts for customers. Functionality and validation testing confirmed that the system eliminates data redundancy, accelerates record retrieval to under three seconds, organizes production tracking, and eradicates cash-flow calculation discrepancies. This research demonstrates how the transition from manual ledger systems to localized web frameworks significantly optimizes workflows and service reliability within micro-enterprises